Effects of uncertainty factors and refurbishment projects performance in relation to leadership quality of project managers - R. Yacob,; I. Rahmat,; M. Saruwono,; Z. Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Refurbishment projects vary in scope of work compared to the new projects. The key features are unique, inherent with uncertainty factors, difficult to achieve high performance and filled with existing leadership quality of project manager issues. This research aims to establish the relationship between refurbishment project uncertainty factors and refurbishment project performance in relation to the quality of leadership among project managers. The objective of this research is to measure the level of uncertainty factors of building refurbishment projects, to determine the performance of building refurbishment projects, to identify the leadership quality of refurbishment project managers and to analyse the relationship between refurbishment project uncertainty factors and project performance in relation to leadership quality of refurbishment project managers. The quantitative research method was adopted in this research and analysed using descriptive and correlation analysis via IBM SPSS version 22, 130 questionnaires were distributed to the target group of Project Managers involved in building refurbishment and registered with CIDB in the Klang Valley, Malaysia, with contract value starting from RM500,000. 35 responses were found to be suitable to form a database for analysis. The results conclude that there were significance relationships between the groups of variables in the conceptual framework, thus, contribute in managing uncertainties factors of building refurbishment projects through leadership qualities among project managers and for furthered research in this area.